A case of a right diaphragm rupture developed after blunt trauma - Demircan, Sedat; Uzar, Ali; Tastepe, Irfan; Kurkcuoglu, Can; Alper, Aysin; Unlu, Mehmet (Annals of Medical Research, 2021)
None
Keywords: s : Diaphragm rupture, blunt trauma